2015
DOI: 10.1590/2317-1545v37n3149549
|View full text |Cite
|
Sign up to set email alerts
|

Moisture desorption isotherms of cucumber seeds: modeling and thermodynamic properties

Abstract: -Hygroscopic equilibrium curves or sorption isotherms are important in order to define dehydration limits of the product, estimate moisture content alterations under environment conditions and to acquire moisture content values for safe storage. This work aimed to determine desorption isotherms of cucumber seeds stored at different temperature (10, 20, 30, 40 and 50 ºC) and relative humidity (0.11 to 0.96) and the thermodynamic properties of this process. Mathematical models were fitted to experimental data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 24 publications
(20 reference statements)
5
20
0
7
Order By: Relevance
“…These results corroborate those obtained by Corrêa et al (2015), who observed increase in the equilibrium moisture content of coffee (Coffea canephora) fruits as a function of water activity for a specific temperature, and its reduction with the increase of temperature for a certain water activity, in both desorption and adsorption. The reduction in the equilibrium moisture content with the increase in temperature can be justified based on the increase of the water vapor pressure in the air and on the surface of the product (Campos et al, 2009).…”
Section: Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…These results corroborate those obtained by Corrêa et al (2015), who observed increase in the equilibrium moisture content of coffee (Coffea canephora) fruits as a function of water activity for a specific temperature, and its reduction with the increase of temperature for a certain water activity, in both desorption and adsorption. The reduction in the equilibrium moisture content with the increase in temperature can be justified based on the increase of the water vapor pressure in the air and on the surface of the product (Campos et al, 2009).…”
Section: Methodssupporting
confidence: 92%
“…Important post-harvest steps include fruit drying and storage and, to correctly perform these operations, it is essential to know the relationships existing between the product and the surrounding air (Corrêa et al, 2015). The conservation of quality of the products depends on the environmental conditions of relative humidity and temperature under which they will be stored (Borges et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Gibbs free energy increases with decreasing moisture content, being positive for all temperatures studied, with a tendency to stabilize at higher levels of equilibrium moisture content. This behavior was also observed by Corrêa et al (2015) and by Sousa et al (2015) when studying cucumber and fodder radish seeds, respectively. Gibbs free energy is related to the work required to make sorption sites available (Nkolo Meze'e et al, 2008).…”
Section: Table 2 Ratio Between L/l' For the Different Moisture Contesupporting
confidence: 66%
“…These parameters thermodynamic parameters of different seeds, similar in shape and size to lettuce seeds, such as grape seed (Vitis sp) (MAJD et al, 2014), turnip seed (Brassica rapa subsp. rapa) (SOUSA et al, 2015), cucumber seed (Cucumis sativus L.) (CORRÊA et al, 2015) and pepper seed (Capsicum sp) (SILVA et al, 2016). Therefore, even though there is a considerable wealth of literature about thermodynamic properties, information in the thermodynamic properties of lettuce seeds is still emerging.…”
Section: Methodsmentioning
confidence: 99%